Efektivitas Kebijakan Sosial dalam Pemecahan Masalah Sosial - Soetomo, - (Jurnal Ilmu Sosial dan Ilmu Politik, 2011)
Social policy was understood as a response of government toward social problems steam from individuals and systems, as well as social structures and social institutions. Thus the effectiveness of social policies in solving social problems will only be achieved if social policies not only general in changes and improvements at the individual level, but also able to promote social change through institutional and structural transformation. While not ignoring governmentâs role as the main actor, this paper emphasizes the importance of society in fostering social transformation.